Xinfuli granule alleviates metabolic remodeling through inhibition of endoplasmic reticulum stress and mitochondrial injury in heart failure. (1st March 2023) - Su, Yan-Ni; Lu, Pei-Pei; Yan, Si-Yu; Guo, Xuan-Tong; Ma, Jie; Guo, Cai-Xia; Ma, Li-Hong
Abstract: Ethnopharmacological relevance: "Qi deficiency-blood stasis-water retention syndrome" was the most frequent syndrome among heart failure(HF) patients according to Traditional Chinese Medicine (TCM) theory. Xinfuli Granule (XG) was constructed on the basis of classical formula "Baoyuan decoction" to enhance the function of nourishing Qi, activating blood and removing water retention. XG treatment has obtained clinical effect on HF patients. Aim of the study: The regulation of XG on energy metabolism of HF was investigated with special focus on endoplasmic reticulum stress (ERS) and mitochondrial function. Materials and methods: Components of XG was acquired by UPLC/Q-TOF-MS Analysis, left anterior descending ligation(LAD)-induced HF rats model and hypoxia-ischemia(H–I)-induced H9 c2 cells model were constructed to evaluate the effect of XG treatment. Cardiac function was evaluated by echocardiographic parameters, energy metabolism was evaluated by metabolites and ATP/ADP/AMP levels in blood samples, cardiomyocyte morphology and myocardial fibrosis were assessed by HE staining and Masson staining, mitochondrial ultrastructure was observed under Transmission Electron Microscope, viability and apoptosis rate of H9 c2 cells was detected by cell counting kit-8 reaction and flow cytometry analysis, respectively. Mitochondrial membrane potential (MMP) of H9 c2 cells was observed by JC-1 kit under fluorescent microscope, expression of peroxisome-proliferator-activated receptor (PPAR)-coactivator (PGC1α), ERS-related genes and RHOA/ROCK pathway were analysed by Quantitative Real-time PCR (RT-qPCR) and Western Blot. Results: Here, we showed that XG alleviated cardiac metabolic remodeling and stimulated ATP production through elevated expression of PGC1α in HF rats. XG also helped recover mitochondrial deformation and decrease apoptosis rate accompanied by an increase of the Bcl2/Bax ratio and the mitochondrial membrane potential in hypoxia-ischemia (H–I) H9 c2 cells. In addition, we found that XG downregulated ERS-related proteins ATF4, CHOP, Phospho-eIF2α, and Phospho-PERK, and suppressed the RHOA/ROCK pathway, which served as a potential mediator of ERS. Conclusions: we found that XG improved energy production by alleviating mitochondrial injury and inhibiting ERS in heart failures mediated by the RHOA/ROCK pathway. Graphical abstract: Image 1 Highlights: Xinfuli granule restores the energy metabolism disorder and improves ATP production in the heart failure. Xinfuli granule protects the integrity and function of mitochondria against injury. Xinfuli granule alleviates the endoplasmic reticulum stress (ERS) in the heart failure. RHOA/ROCK pathway is a promising target heart failure as it mediates ERS and mitochondrial injury in heart failure.